Defining the terminology and parameters that should be used in studies into dermoscopy for non‐cancer skin diseases. (1st February 2020) - Errichetti, E.; Zalaudek, I.; Kittler, H.; Apalla, Z.; Argenziano, G.; Bakos, R.; Blum, A.; Braun, R.; Ioannides, D.; Lacarrubba, F.; Lazaridou, E.; Longo, C.; et al.
Summary: Dermoscopy is a technique using a handheld magnifying device called a dermatoscope that allows doctors to see structures in the skin that are not visible to the naked eye. This helps with the diagnosis of skin diseases and reduces the need for biopsies (removal of a small sample of skin to be examined under a microscope). Its main use is for skin tumours (e.g. skin cancers), but it is increasingly used also in other skin diseases, especially inflammatory and infectious skin diseases. Over the last few years, several articles on dermoscopy of non‐tumoural (i.e. not cancer) skin diseases have been published, yet there is poor consistency in the terminology (language) used among the different studies. The present study, involving a total of 37 international experts from all over the world on behalf of the International Dermoscopy Society, aimed to identify uniform terms and basic parameters (what doctors should look for) to adopt/evaluate when using dermoscopy in non‐tumoral skin diseases. This aim was achieved by using a standardized agreement procedure (called "modified DELPHI method"). The authors identified five standardized basic parameters. For each of them, possible variables were selected, with a total of 31 different sub‐items. Adopting a structured and uniform method to describe dermoscopic findings will help researchers and will allow different studies to be compared. This is particularly relevant for future studies on dermoscopy in general dermatology, which the authors strongly recommend should be designed using the terminology and parameters outlined in this study. This summary relates to the study: Standardization of dermoscopic terminology and basic dermoscopic parameters to evaluate in general dermatology (non‐neoplastic dermatoses): an expert consensus on behalf of the International Dermoscopy Society